The Effect of Administration of Longan (DimocarpusLonganL Steud)Leaf Extract Cream on Collagen Density and MMP-1 Expression in the Dermis of BALB/C Mice Exposed to UV-B Rays - Maryam Mulyaningsih, Ruri Eka; Hussaana, Atina; Chodidjah, Chodidjah (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2019)
INTRODUCTION: UV-B exposure to the skin may produce ROS, decreasing collagen density and increasing MMP-1 expression. Longan leaf extract cream contains antioxidant and is expected to prevent decrease in collagen density and MMP-1 expression increase.OBJECTIVE: The research aims at administering longan leaf extract cream to increase collagen density and decrease MMP-1 expression in BALB/c mice exposed to UV-B rays.METHODS: This experimental research employed a Post Test Only Controlled Group Design. The subjects were 24 BALB/c mice, which were randomly divided into 4 groups. The Control Group (Ctr-G)was only administered with basic cream and exposed to UV-B rays, while Groups DLS-3, DLS-6, and DLS-13were respectively administered with longan leaf extract cream at doses 3.25%, 6.5% and 13% and exposed to UV-B rays for 4 weeks at a dose of 1 MED. On day 29, a tissue excision biopsy was performed to determine the collagen density and MMP-1 expression. The collagen density preparations were made using Masson’s Trichome staining and MMP-1 preparations were made using immunohistochemical staining.RESULTS: Kruskalwallis analysis showedstatistically no significant differences in collagen density and MMP-1 expression between groups(p value> 0.05).CONCLUSION: Administration of longan leaf extract cream at doses of 3.25%, 6.5% and 13% had proven unable to increase collagen densitynor decrease the MMP-1 expression significantly after UVB exposure.